Effectiveness of Electric Bus Stops on Corridor 5 (Merdeka Square – Tembung) in Medan City - Noviyanti Pakpahan; Anthoni Veery Mardianta; Gina Cynthia Raphita Hasibuan (Ali Institute or Research and Publication, 2026)
Good public transport services are determined not only by the operational performance of vehicles, but also by the quality of bus stop facilities that are safe, comfortable and easily accessible to the public. The method used in this study is an analysis of operational performance based on the Decision of the Director General of Land Transportation No. 271/HK.105/DRJD/96 through a survey conducted on board buses, using parameters including load factor, headway, journey time, and vehicle stopping time. In addition, the Importance Performance Analysis (IPA) and SWOT methods were used to evaluate the level of bus stop service based on user perceptions. Data processing was carried out using IBM SPSS software. The results of the study indicate that the operational performance of public transport is relatively good but not yet optimal. Vehicle stopping time and travel time between bus stops are relatively efficient; however, load factors and the distance between buses still show variation, indicating that service regularity is not yet fully consistent. The IPA analysis reveals that the importance score (MIS) is higher than the performance/satisfaction score (MSS), suggesting that bus stop services have not yet fully met user expectations